Defense Mechanisms and Self-Control in Recovering Substance Abuse Clients - Farhana Sabri; Nur Afidah Abdullah; Mohd Khairul Anuar (Universiti Sains Islam Malaysia, 2024)
The appraisal of defense mechanisms and self-control in recovery substance abuse clients in Malaysia is vital as it provides self-support for maintaining recovery. This study aims to investigate types of defense mechanisms in recovering substance abuse clients and its relation to self-control level. The study was carried out on 138 respondents. The respondents were randomly selected among recovering substance abuse clients in a rehabilitation centre. The data indicated that neurotic defence mechanisms (M=14.29, SD=3.93) are the most prominent among the respondents. Meanwhile, the respondents' self-control scored at average level (M=47.03, SD = 8.76). There was a positive correlation between immaturity defense style and self-control (r = 0.36, p = 0.0). This study concludes that with continued treatment and support, they can remain in recovery and sober.